Molecular Docking for chitosan, salicylaldoxime and 3-Chloro aniline act as an Estrogen Receptor (β) in MCF-7 Cell line. - P.Sivarajani; R.Ida Malarselvia; R. Pricillab; C. Ramachandra Raja (The Bioscan, 2024)
Computational modeling of the structure created by multiple interacting molecules is known as molecular docking. Molecular docking software is mostly utilized for new drug confirmation and medication enhancement. Salicylaldoxime already functions as an estrogen receptor, and the anti-cancer properties were enhanced by the combination of pure chitosan and 3-chloro aniline. A new one (E)(2R, 3R, 4S, and 6R) -2-hydroxybenzaldehyde O-(3-amino -6-(E)-(imino)methyl(3-chloropheyl)-2H-pyran-4-yl -2-5-dimethoxytetrahydroTo assess anticancer efficacy against the MCF-7 breast cancer cell line, oxime (CS-ClA) was produced. Domine (PDB ID: 1QKM, 1X7R, 1X78, 2nV7, 3ERT, 7KBS, 3UUD, 3BQT, 5TOA, 6PRD) is bound by the CS-ClA estrogen receptor ligand. The docking capacity in binding affinities for new compounds is impacted by the interaction between the sampling and scoring functions in the Docking Assessment.